(untitled) (Research, Society and Development, 2024)
The objective of this work was to quantify the production and absorption of nutrients by chickpeas due to the application of doses of limestone on the surface to increase base saturation. The work was conducted at the UniEvangélica experimental unit. The experimental design adopted was randomized blocks, with four treatments and four replications, each replication with five lines of plants, spaced 0.65 m apart with plots of 6.5 m2, with 12 plants per linear m. The treatments were: T1 – Control (V = 60%); T2 –V2 =70%; T3 –V2 =100%; T4 –V2 =150%. To evaluate leaf mineral composition, leaf samples were collected at the beginning of flowering. Height, grain yield and agronomic efficiency were evaluated at the end of the cycle. The evaluated parameters were subjected to analysis of variance, and when significant differences occurred, the Tukey mean test was applied. Plant height showed no statistical differences. Macronutrient accumulation was N > K > Ca > Mg > P > S. And micronutrients Fe > Mn > Zn > B > Cu. The increase in base saturation influenced agronomic efficiency. The chickpea cultivar BRS Cristalino presents better agronomic performance at the highest technical lime efficiency dosage of 3.58 t ha-1. Base saturation of 60 to 70% presents high agronomic efficiency and can be adopted as a parameter for recommending liming for chickpeas.